(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Physical education (PE) in India plays a vital role in promoting accessibility and inclusion for children with disabilities. Beyond physical activity, inclusive PE fosters social and emotional growth, enhancing self-worth and community among students. Despite challenges like limited resources, inadequate professional development, and societal biases, inclusive PE is essential for equitable education. Collaboration among policymakers, communities, and schools is crucial to overcoming these obstacles. By investing in accessible facilities, adaptive equipment, and ongoing teacher training, we can create a learning environment where all students, regardless of ability, thrive and are celebrated for their diversity.